Contemporary Emigration of Croats: What is the Future of the Republic of Croatia? - Jerić, Marijana (Oeconomica Jadertina, 2019)
The Republic of Croatia has seen several large emigration waves throughout history. The last wave of emigration began with the accession of the Republic of Croatia to the European Union in 2013 and continues today. Developed European Union countries such as Germany, Austria and Ireland have become a major destination for Croatian expatriates in search of a better life. The aim of this research is to determine the actual status of the number of Croat emigrants from the Republic of Croatia, to compare the data with the official statistics of the Republic of Croatia and to conclude on the possible consequences of emigration. The results of the research show that the emigration of Croatian citizens cannot be monitored according to the official data of the Central Bureau of Statistics because they are not harmonized with the statistics of the emigration countries, i.e. the number of reported Croatian immigrants is on average 62% higher than the official data of the Republic of Croatia. Forecasts of future migration of Croatian citizens indicate that 20% of the population will lose over the next 30 years, which is why it is already necessary to develop new economic, pension, education and other policies that affect demographic change.
Keywords: Croat emigration; external migration; emigration; demography; future of Croatia